Composite catalyst, electrode loaded with composite catalyst as well as preparation method and application of electrode
By supporting the composite catalyst on the electrode, the problems of poor dispersion and low catalytic activity of metal complex catalysts in CO2 electroreduction are solved, and higher catalytic activity and product selectivity are achieved.
Patent Information
- Application Number
- CN202311110492.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The application of metal complex catalysts in CO2 electroreduction is limited by poor dispersion and low catalytic activity, resulting in insufficient efficiency and selectivity of CO2 conversion to CO2.
A composite catalyst is used, which consists of polymer-coated metalporphyrin and aminoimidazole-containing ionic liquid polymer to form a bilayer polymer structure and is supported on the electrode.
The electron density and dispersion of the catalyst activity center are improved, the binding ability with CO2 is enhanced, and the catalytic activity and target product selectivity of the electrocatalytic reaction are improved.
Smart Images

Figure CN119530876A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of electrochemical catalysis, and in particular, to a composite catalyst, an electrode loaded with the composite catalyst, and a preparation method and application thereof. Background Art
[0002] The excessive emission of carbon dioxide (CO2) increases the pressure on the natural carbon cycle, leading to a serious greenhouse effect. The electrocatalytic CO2 reduction reaction (CO2RR) provides a feasible method for converting renewable electricity into high-value-added fuels and chemical raw materials in the form of storage in chemical bonds. Among the different products of CO2RR, the conversion of CO2 to CO is considered to be one of the most promising reactions in the chemical industry due to its technical and economic feasibility. Due to the high chemical inertness of CO2 molecules, the research on efficient and low-cost electrocatalysts has attracted widespread attention.
[0003] In recent years, many researchers have applied metal complex catalysts to the efficient electrocatalytic reduction of carbon dioxide. Molecular catalysts have clear active sites and precisely tailored structures, which can achieve high Faraday efficiency and selectivity for the electrocatalytic CO2 to CO reaction. However, metal complex molecules are more likely to form π-π stacking, resulting in poor dispersion and catalytic activity, which severely limits the application of metal complex catalysts in CO2 electroreduction. Summary of the invention
[0004] The purpose of the present disclosure is to provide a composite catalyst, an electrode loaded with the composite catalyst, and a preparation method and application thereof, so as to improve the catalytic activity and target product selectivity of electrocatalytic CO2 reduction to CO.
[0005] In order to achieve the above-mentioned object, the present disclosure provides a composite catalyst in a first aspect, comprising a first polymer material and a second polymer material, wherein the first polymer material is a polymer-encapsulated and coordinated metal porphyrin, and the second polymer material is an aminoimidazole-containing ionic liquid polymer; the polymer-encapsulated and coordinated metal porphyrin has a repeating unit as shown in formula (1):
[0006]
[0007] Wherein, M is Co, Cu, Ni or Fe, R is selected from amino, hydroxyl, alkoxy or amide, and L is selected from pyridyl, 2-methylpyridyl or imidazole.
[0008] Optionally, the aminoimidazole-containing ionic liquid polymer is one or more selected from poly(1-vinyl-3-aminopropylimidazole) bromide, poly(3-ethylamino-1-butylimidazole) bromide, poly(1-propylamino-3-methylimidazole) nitrate, poly(1-propylamino-3-butylimidazole) bromide, poly(1-propylamino-3-butylimidazole) tetrafluoroborate, poly(1-ethylamino-3-methylimidazole) nitrate, poly(1-ethylamino-3-methylimidazole) bromide and poly(1-ethylamino-3-methylimidazole) tetrafluoroborate.
[0009] Optionally, the weight ratio of the first polymer material to the second polymer material is (0.5-5):1.
[0010] Optionally, the composite catalyst is formed into a layered structure, and the first polymer material and the second polymer material are distributed in layers.
[0011] In a second aspect of the present disclosure, a method for preparing an electrode loaded with a composite catalyst is provided, wherein the composite catalyst is the composite catalyst described in the first aspect of the present disclosure, and the method comprises the following steps:
[0012] Respectively obtain an electrode substrate, the first polymer material and the second polymer material;
[0013] Applying a first mixed solution containing the first polymer material and a first solvent to the electrode substrate, and then performing a first drying to obtain an electrode loaded with the first polymer material;
[0014] A second mixed solution containing the second polymer material and a second solvent is applied to the electrode loaded with the first polymer material, and then a second drying is performed to obtain an electrode loaded with a composite catalyst.
[0015] Optionally, the electrode substrate is at least one of carbon paper, glassy carbon electrode, carbon cloth and graphite electrode.
[0016] Optionally, the weight ratio of the first polymer material to the first solvent is 1:(50-150);
[0017] The weight ratio of the second polymer material to the second solvent is 1:(50-150).
[0018] Optionally, the first drying conditions include: a temperature of 60 to 80° C. and a time of 20 to 40 minutes;
[0019] The second drying conditions include: a temperature of 60 to 80° C. and a time of 20 to 40 minutes.
[0020] In a third aspect of the present disclosure, there is provided an electrode loaded with a composite catalyst prepared by the method described in the second aspect of the present disclosure.
[0021] In a fourth aspect of the present disclosure, there is provided use of the electrode loaded with the composite catalyst described in the third aspect of the present disclosure in electrocatalytic production of CO.
[0022] Through the above technical scheme, the composite catalyst disclosed in the present invention has a double-layer polymer structure, and the electrode loaded with the composite catalyst is suitable for the electrochemical catalytic CO2 reduction to CO process. On the one hand, it has a higher electron density of the catalyst active center and good dispersibility, which can enhance the binding ability with the reactant CO2; on the other hand, it is conducive to adsorbing CO2 in the electrolyte and increasing the local CO2 concentration around the catalyst, thereby effectively improving the catalytic activity and target product selectivity of the electrocatalytic reaction. The preparation process of the electrode loaded with the composite catalyst is simple and low-cost, which lays a good foundation for mass production in practical applications.
[0023] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0025] Figure 1 A schematic diagram of the structure of an electrode loaded with a composite catalyst according to a specific embodiment of the present disclosure.
[0026] Figure 2 This is an X-ray absorption near edge structure (XANES) spectrum of the first polymer material in Example 1 (poly (4-vinylpyridine) coordinated methoxyphenylporphyrin cobalt).
[0027] Description of Reference Numerals
[0028] 1 - electrode substrate 1, 2 - first polymer material layer, 3 - second polymer material layer. DETAILED DESCRIPTION
[0029] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0030] In a first aspect, the present disclosure provides a composite catalyst, comprising a first polymer material and a second polymer material, wherein the first polymer material is a polymer-encapsulated and coordinated metal porphyrin, and the second polymer material is an aminoimidazole-containing ionic liquid polymer; the polymer-encapsulated and coordinated metal porphyrin has a repeating unit as shown in formula (1):
[0031]
[0032] Wherein, M is Co, Cu, Ni or Fe, R is selected from amino, hydroxyl, alkoxy or amide, wherein the number of carbon atoms of the alkoxy or amide can be 1 to 2, and L is selected from pyridyl, 2-methylpyridyl or imidazole. Further, M is preferably Co or Ni, most preferably Co, and R is preferably amino, hydroxyl or methoxy. Optionally, the polymer-coated and coordinated metal porphyrin is selected from at least one of methoxyphenylporphyrin cobalt coordinated by poly-4-vinylpyridine, methoxyphenylporphyrin nickel coordinated by poly-4-vinylpyridine, aminophenylporphyrin cobalt coordinated by polyimidazole, aminophenylporphyrin nickel coordinated by polyimidazole, and aminophenylporphyrin cobalt coordinated by poly-4-vinylpyridine. The weight average molecular weight of the first polymer material can be 100,000 to 200,000 g / mol.
[0033] Optionally, the aminoimidazole-containing ionic liquid polymer can be one or more selected from poly(1-vinyl-3-aminopropylimidazole) bromide, poly(3-ethylamino-1-butylimidazole) bromide, poly(1-propylamino-3-methylimidazole) nitrate, poly(1-propylamino-3-butylimidazole) bromide, poly(1-propylamino-3-butylimidazole) tetrafluoroborate, poly(1-ethylamino-3-methylimidazole) nitrate, poly(1-ethylamino-3-methylimidazole) bromide and poly(1-ethylamino-3-methylimidazole) tetrafluoroborate. Further, the aminoimidazole-containing ionic liquid polymer is one or more selected from poly(3-ethylamino-1-butylimidazole) bromide, poly(1-propylamino-3-methylimidazole) nitrate, poly(1-propylamino-3-butylimidazole) bromide and poly(1-ethylamino-3-methylimidazole) nitrate. The weight average molecular weight of the second polymer material can be 10,000 to 30,000 g / mol.
[0034] The weight ratio of the first polymer material to the second polymer material may be (0.5-5):1, preferably (1-3):1.
[0035] In one embodiment, the composite catalyst is formed into a layered structure, and the first polymer material and the second polymer material are stacked and distributed. The first polymer material and the second polymer material are stacked and distributed, which means that the first polymer material can be formed into a first polymer material layer, the second polymer material can be formed into a second polymer material layer, the first polymer material layer is stacked on the second polymer material layer, or the second polymer material layer is stacked on the first polymer material layer.
[0036] In a second aspect of the present disclosure, a method for preparing an electrode loaded with a composite catalyst is provided, wherein the composite catalyst is the composite catalyst described in the first aspect of the present disclosure, and the method comprises the following steps S1 to S3:
[0037] S1. Obtaining an electrode substrate, the first polymer material and the second polymer material respectively;
[0038] S2, applying a first mixed solution containing the first polymer material and a first solvent to the electrode substrate, and then performing a first drying to obtain an electrode loaded with the first polymer material;
[0039] S3, applying a second mixed solution containing the second polymer material and a second solvent to the electrode loaded with the first polymer material, and then performing a second drying to obtain an electrode loaded with a composite catalyst.
[0040] In step S1, the electrode substrate may be at least one of carbon paper, glassy carbon electrode, carbon cloth and graphite electrode.
[0041] The first polymeric material (ie, polymer-encapsulated and coordinated metalloporphyrin) and the second polymeric material (ie, aminoimidazole-containing ionic liquid polymer) can each be commercially available or prepared using existing methods, and the present disclosure has no particular limitations.
[0042] In step S2, the first solvent may be a common polar organic solvent, such as dimethylformamide, dimethyl sulfoxide, dichloromethane, etc.; the weight ratio of the first polymer material to the first solvent may be 1:(50-150). The first mixed solution may be applied to the electrode substrate by dripping or coating, and preferably multiple applications are performed, and the first drying is performed after each application, and then the next application is performed. The conditions for the first drying may include: a temperature of 60-80°C and a time of 20-40 minutes. After step S2, the first polymer material is formed into a first polymer material layer loaded on the electrode substrate.
[0043] In step S3, the second solvent may be a common organic solvent, such as dimethylformamide, anhydrous ethanol, chloroform, etc.; the weight ratio of the second polymer material to the second solvent may be 1:(50-150). Preferably, the second polymer material is mixed with the second solvent and fractionated under ultrasonic conditions to obtain the second mixed solution, and the ultrasonic time may be 15-45 minutes. The second mixed solution may be applied to the electrode loaded with the first polymer material by dripping or coating, preferably multiple times, and the second drying is performed after each application, and then the next application is performed. The conditions for the second drying may include: a temperature of 60-80°C and a time of 20-40 minutes. After step S3, the second polymer material is formed into a second polymer material layer, which is coated on the first polymer material layer, and finally an electrode loaded with a composite catalyst is obtained.
[0044] In a third aspect of the present disclosure, there is provided an electrode loaded with a composite catalyst prepared by the method described in the second aspect of the present disclosure. Figure 1 As shown, the electrode loaded with the composite catalyst comprises an electrode substrate 1, a first polymer material layer 2 and a second polymer material layer 3 which are stacked in sequence.
[0045] In a fourth aspect of the present disclosure, there is provided use of the electrode loaded with the composite catalyst described in the third aspect of the present disclosure in electrocatalytic production of CO.
[0046] The composite catalyst disclosed in the present invention has a double-layer polymer structure and is suitable for electrochemical catalytic CO2 reduction to CO. On the one hand, it has a higher electron density of the catalyst active center and good dispersibility, which can enhance the binding ability with the reactant CO2; on the other hand, it is conducive to adsorbing CO2 in the electrolyte and increasing the local CO2 concentration around the catalyst, thereby effectively improving the catalytic activity and target product selectivity of the electrocatalytic reaction. The preparation process of the electrode loaded with the composite catalyst is simple and low-cost, which lays a good foundation for mass production in practical applications.
[0047] The present disclosure is further described below in conjunction with specific embodiments, which are only part of the embodiments of the present disclosure, rather than all of the embodiments. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present disclosure can be purchased from the market or prepared by existing methods.
[0048] Example 1
[0049] (1) Obtain an electrode substrate, a first polymer material, and a second polymer material respectively.
[0050] The first polymer material is cobalt methoxyphenylporphyrin coordinated with poly-4-vinylpyridine, which is obtained by coordinating cobalt methoxyphenylporphyrin with poly-4-vinylpyridine. It has a repeating unit as shown below, a weight average molecular weight of 160000 g / mol, and a XANES diagram as shown below. Figure 2 ;
[0051]
[0052] The second polymer material is poly(3-ethylamino-1-butylimidazole) bromide, and the weight average molecular weight is 25000 g / mol;
[0053] The electrode substrate is a carbon paper electrode.
[0054] (2) Preparation of electrodes loaded with composite catalysts
[0055] 20 μL of a first mixed solution containing a first polymer material and a first solvent dimethylformamide (weight ratio of 1:98) was taken and dripped onto a carbon paper electrode four times. After each dripping, the carbon paper electrode was placed in a drying oven at 65° C. to evaporate the solution to obtain an electrode loaded with the first polymer material;
[0056] 1 wt % poly(3-ethylamino-1-butylimidazole) bromide was dissolved in anhydrous ethanol as a second solvent (the weight ratio of poly(3-ethylamino-1-butylimidazole) bromide to the second solvent was 1:100), and ultrasonicated at room temperature for 30 min to obtain a second mixed solution. 20 μL of the second mixed solution was added dropwise onto the electrode loaded with the first polymer material four times. After each addition, the electrode was placed in a drying oven at 65° C. to evaporate the solution to dryness, and finally the electrode loaded with the composite catalyst prepared in this embodiment was obtained, wherein the composite catalyst is as follows: Figure 1 In the layered structure shown, the weight ratio of the first polymeric material to the second polymeric material is 1.02:1 (on a dry basis).
[0057] Example 2
[0058] An electrode loaded with a composite catalyst was prepared according to the method of Example 1, except that the first polymer material was replaced by methoxyphenylporphyrin nickel coordinated with poly-4-vinylpyridine, and methoxyphenylporphyrin nickel was coordinated with poly-4-vinylpyridine to obtain a composite catalyst having a repeating unit as shown below, and a weight average molecular weight of 160000 g / mol.
[0059]
[0060] Example 3
[0061] An electrode loaded with a composite catalyst was prepared according to the method of Example 1, except that the first polymer material was replaced by aminophenylporphyrin cobalt coordinated with polyvinylimidazole, and aminophenylporphyrin cobalt was coordinated with polyvinylimidazole to obtain a composite catalyst having a repeating unit as shown below, and a weight average molecular weight of 160000 g / mol.
[0062]
[0063] Example 4
[0064] An electrode loaded with a composite catalyst was prepared according to the method of Example 1, except that the second polymer material was replaced by poly(1-vinyl-3-aminopropylimidazole) bromide having a weight average molecular weight of 25000 g / mol.
[0065] Example 5
[0066] An electrode loaded with a composite catalyst was prepared according to the method of Example 1, except that, in step (2), 10 μL of the first mixed solution was added dropwise onto a carbon paper electrode twice, and after each addition, the carbon paper electrode was placed in a drying oven at 65°C to evaporate the solution to obtain an electrode loaded with a first polymeric material, and then 20 μL of the second mixed solution was added dropwise onto the electrode loaded with the first polymeric material four times, and after each addition, the electrode was placed in a drying oven at 65°C to evaporate the solution to obtain the electrode loaded with a composite catalyst prepared in this example, wherein the weight ratio of the first polymeric material to the second polymeric material was 0.51:1 (on a dry basis).
[0067] Example 6
[0068] An electrode loaded with a composite catalyst was prepared according to the method of Example 1, except that, in step (2), 20 μL of the first mixed solution was added dropwise onto a carbon paper electrode in four times, and after each addition, the carbon paper electrode was placed in a drying oven at 65°C to evaporate the solution to obtain an electrode loaded with a first polymer material, and then 5 μL of the second mixed solution was added dropwise onto the electrode loaded with the first polymer material, and after each addition, the electrode was placed in a drying oven at 65°C to evaporate the solution to obtain the electrode loaded with a composite catalyst prepared in this example, wherein the weight ratio of the first polymer material to the second polymer material was 4.08:1 (on a dry basis).
[0069] Comparative Example 1
[0070] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (3), the second polymer material was not loaded, that is, the electrode prepared in this comparative example was an electrode loaded with the first polymer material.
[0071] Test Example
[0072] The electrode prepared in the embodiment and the comparative example is applied as a cathode to the electrocatalytic reduction of CO2 to produce CO, and the reaction conditions include: the electrochemical reaction is carried out in a double-chamber H-type electrolytic cell separated by a cation exchange membrane (Nafion 117). The electrolytic cell uses a three-electrode system, which is closed and connected to an electrochemical workstation for measurement. A saturated calomel electrode and a platinum sheet electrode are used as a reference electrode and a counter electrode, respectively, and a carbon paper loaded with a composite catalyst is used as a working electrode. An aqueous solution of 0.5 mol / L sodium bicarbonate saturated with CO2 is used as an electrolyte. The reaction voltage is set to -1.25 V (relative to a saturated calomel electrode), and the reaction time is 2 h.
[0073] The CO Faraday efficiency and CO2RR current density were calculated according to the following formula. The results are shown in Table 1.
[0074] CO Faraday efficiency (%) FE CO =(V HS ×CCO ×2F) / (V×Q)×100%
[0075] CO2RR current density = [Q / (t×A)]×FE CO
[0076] Among them, V HS is the headspace volume of the electrolytic cell (mL), C CO is the volume concentration of CO (%), F is the Faraday constant (F = 96485C / mol), V is the gas molar volume at 25°C and 1.0atm (24.5L / mol), Q is the charge of the electrolysis reaction (C), t is the time of the electrolysis reaction (s), and A is the area of the working electrode (cm 2 ).
[0077] Table 1
[0078] <![CDATA[CO Faraday efficiency FE CO , %]]> <![CDATA[CO2RR current density, mA / cm 2 > Example 1 98.0 20.6 Example 2 91.8 17.7 Example 3 93.7 18.9 Example 4 94.6 18.4 Example 5 90.2 18.2 Example 6 92.5 17.3 Comparative Example 1 88.7 13.5
[0079] As can be seen from Table 1, the electrode using the loaded composite catalyst of the present invention has a higher CO Faraday efficiency and CO2RR current density, indicating that the electrode using the loaded composite catalyst of the present invention can significantly improve the target product selectivity and catalytic activity of electrocatalytic CO2 reduction to CO.
[0080] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0081] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0082] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A composite catalyst, characterized in that: The composite catalyst comprises a first polymer material and a second polymer material, wherein the first polymer material is a polymer-encapsulated and coordinated metal porphyrin, and the second polymer material is an aminoimidazole-containing ionic liquid polymer; the polymer-encapsulated and coordinated metal porphyrin has a repeating unit as shown in formula (1): Wherein, M is Co, Cu, Ni or Fe, R is selected from amino, hydroxyl, alkoxy or amide, and L is selected from pyridyl, 2-methylpyridyl or imidazole.
2. The composite catalyst according to claim 1, wherein The amino imidazole-containing ionic liquid polymer is one or more selected from poly(1-vinyl-3-aminopropyl imidazole) bromide, poly(3-ethylamino-1-butyl imidazole) bromide, poly(1-propylamino-3-methyl imidazole) nitrate, poly(1-propylamino-3-butyl imidazole) bromide, poly(1-propylamino-3-butyl imidazole) tetrafluoroborate, poly(1-ethylamino-3-methyl imidazole) nitrate, poly(1-ethylamino-3-methyl imidazole) bromide and poly(1-ethylamino-3-methyl imidazole) tetrafluoroborate.
3. The composite catalyst according to claim 1, wherein The weight ratio of the first polymer material to the second polymer material is (0.5-5):
1.
4. The composite catalyst according to claim 1, wherein The composite catalyst is formed into a layered structure, and the first polymer material and the second polymer material are distributed in layers.
5. A method for preparing an electrode loaded with a composite catalyst, wherein: The composite catalyst is a composite catalyst according to any one of claims 1 to 4, characterized in that the method comprises the following steps: Respectively obtain an electrode substrate, the first polymer material and the second polymer material; Applying a first mixed solution containing the first polymer material and a first solvent to the electrode substrate, and then performing a first drying to obtain an electrode loaded with the first polymer material; A second mixed solution containing the second polymer material and a second solvent is applied to the electrode loaded with the first polymer material, and then a second drying is performed to obtain an electrode loaded with a composite catalyst.
6. The method according to claim 5, wherein: The electrode substrate is at least one of carbon paper, glassy carbon electrode, carbon cloth and graphite electrode.
7. The method according to claim 5, wherein: The weight ratio of the first polymer material to the first solvent is 1:(50-150); The weight ratio of the second polymer material to the second solvent is 1:(50-150).
8. The method according to claim 5, wherein: The first drying conditions include: a temperature of 60 to 80° C. and a time of 20 to 40 minutes; The second drying conditions include: a temperature of 60 to 80° C. and a time of 20 to 40 minutes.
9. An electrode loaded with a composite catalyst prepared by the method according to any one of claims 5 to 8.
10. Use of the electrode loaded with a composite catalyst according to claim 9 in electrocatalytic production of CO.